Volume 3: Design and Analysis 2012
DOI: 10.1115/pvp2012-78767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PWR Primary Water on LCF Behavior of Type 304L Austenitic Stainless Steel at 300°C: Comparison With Results Obtained in Vacuum or in Air

Abstract: Nowadays, it is well known that the low cycle fatigue (LCF) life of austenitic stainless steels can be affected in specific conditions of temperature, strain rate, strain amplitude or dissolved oxygen concentration by the effect of Pressurized Water Reactor (PWR) primary coolant environment. Nevertheless, questions remain about the best methodology that must be used to consider environmental effects for nuclear power plant licensing and for operating lifetime extensions. These environmental effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Therefore, the longer fatigue life obtained with the SIS A signal seems consistent when compared with the results in air presented in the previous section and indicating a less extend of damage with the SIS A signal. These trends are furthermore in agreement with similar data previously obtained on a different grade of 304L [12,17], even though the fatigue resistance of these two alloys are different.…”
Section: Influence Of Strain Rate And/or Complex Loading On Cyclic Besupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the longer fatigue life obtained with the SIS A signal seems consistent when compared with the results in air presented in the previous section and indicating a less extend of damage with the SIS A signal. These trends are furthermore in agreement with similar data previously obtained on a different grade of 304L [12,17], even though the fatigue resistance of these two alloys are different.…”
Section: Influence Of Strain Rate And/or Complex Loading On Cyclic Besupporting
confidence: 92%
“…However, it must be kept in mind that the value of the applied strain In order to examine in more details, the influence of this loading signal and in particular of the slowest part (segment 4), different combinations of these elementary segments have been considered in previous studies [15][16][17]. The results indicated that the signals where the longest segment 4 is applied in tension, that means with a positive deformation, are more damaging than the signals where this slow strain rate segment is applied in the compressive part of the cycle, that means with a negative deformation [12]. In the present study, only the so-called SIS B signal, presented in Figure 3b, will be considered in addition to the SIS A signal.…”
Section: Test Proceduresmentioning
confidence: 97%
See 2 more Smart Citations
“…Fatigue life of stainless steels in high-temperature coolant water of nuclear power plants is shorter than that in air. [1][2][3] To take the reduction in fatigue life into account for component designs, the fatigue life correction factor F en , which is the parameter representing the ratio of fatigue life in air to that in the environment, has been proposed. 1 Through extensive test campaigns, the value of F en has been determined empirically and summarized in assessment guidelines, such as the fatigue assessment guideline issued by the Japan Society of Mechanical Engineers (JSME) 4 (hereafter, called JSME code) and the Boiler and Pressure Vessel Code of the American Society of Mechanical Engineers.…”
Section: Introductionmentioning
confidence: 99%